2019
DOI: 10.1111/bcp.14092
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase inhibitors (TKIs) used in the management of chronic myeloid leukaemia are associated with haematologic toxicities—Which TKI is the safest?

Abstract: Tyrosine kinase inhibitors (TKIs) used in the management of chronic myeloid leukaemia are associated with haematologic toxicities-Which TKI is the safest? Before imatinib, patients with chronic myeloid leukaemia (CML) received hydroxycarbamide, or interferon-alpha alone or in combination with low-dose cytarabine. Younger and fit patients with a suitable donor could be allografted, which was the only potentially therapeutic approach that would result in long-term disease-free survival; however, substantial morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These drugs are highly efficacious in the treatment of leukemia, especially in CML and Ph+ ALL patients. Subsequently, TKIs are becoming a targeted approach and serving as an effective therapeutic plan for those patients with a variety of drug generation options [ 19 , 20 ]. DASA, as a member of the second-generation TKIs, was approved for the treatment of all CMLs and Ph + ALL patients, especially in cases of imatinib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are highly efficacious in the treatment of leukemia, especially in CML and Ph+ ALL patients. Subsequently, TKIs are becoming a targeted approach and serving as an effective therapeutic plan for those patients with a variety of drug generation options [ 19 , 20 ]. DASA, as a member of the second-generation TKIs, was approved for the treatment of all CMLs and Ph + ALL patients, especially in cases of imatinib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, during the early stages of treatment, commercially available TKI might cause toxicity, including myelosuppression and cytopenia [11] . A higher grade of myelosuppression (grade III-IV) is generally seen in the initial stage of treatment and declines dramatically with longer duration of therapy [12] . Despite these findings, neither CML nor management with TKI triggers clinically significant immunosuppression in the chronic phase [5,10,13] .…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the fact that second-generation TKIs (2GTKIs) are more potent than imatinib, inducing more rapid and profound responses with lower rates of transformation to advanced disease, these drugs are often considered as a better treatment option over imatinib in the upfront setting. Besides the potency and efficacy of these drugs, 2GTKIs can be associated with both hematologic and nonhematologic toxicities [3,4], which might interfere with patient health related quality of life [5]. In addition to targeting BCR-ABL1, 2GTKIs also inhibit other kinases and most of the nonhematologic adverse events (AEs) of these drugs are thought to be due to these off-target effects.…”
Section: Introductionmentioning
confidence: 99%